KONTESTASI IDEOLOGI DALAM PELARANGAN CADAR DI PERGURUAN TINGGI ISLAM - Zainal Abidin (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2021)
This study aims to analyze the real reasons for banning the veil (niqab) in freedom of religious expression and the ideological contestation behind the pros and cons of banning the veil on campuses of state Islamic universities. This study used a qualitative design. The data was collected from many online news and social media, which were then analyzed through three stages: data statement, description, and interpretation. This research reveals that the policy of banning the veil on students of state Islamic tertiary institutions is intended to foster students, so they are not exposed to radicalism and extremism. The pros and cons of this policy are based on the contestation of moderatism and radicalism, framed by various constitutional narratives, human rights, and others. Each is interested in ensuring the continuity of his ideology through students who will inherit the leadership of this nation in the future.